Mathematical Formulation Of Instability Of A Subsea Suspendent Pipeline - Mastanzade, Nijat; Yılmaz, Levent (Journal Vibroengineering, Geliu Ratas 15 A, Kaunas, Lt-50282, Lithuania, 2010)
Lateral vibration of underwater suspended pipeline was investigated for the case of pipeline oscillation due to vortex shedding. Firstly, tension force was defined at the connection legs on sea bottom. To define the dynamical equation the analogy of the Mathieu equation was applied, meanwhile Ince-Strutt diagram was used for its solution. As a numerical example we used the behavior of pipeline in a project between Turkey and North Cyprus in the East Mediterranean Sea. Good agreement was found between the theoretical results and experimental data of Danish Hydraulic Institute (DHI).
Keywords: Subsea pipeline; dynamic behavior; Ince-Strutt diagram; oscillation; dynamic stability; beams; denizaltı boru hattı; dinamik davranışı; salınım; dinamik denge; kirişler